2019
DOI: 10.1107/s2053229618016923
|View full text |Cite
|
Sign up to set email alerts
|

The surprising pairing of 2-aminoimidazo[1,2-a][1,3,5]triazin-4-one, a component of an expanded DNA alphabet

Abstract: Supporting information: this article has supporting information at journals.iucr.org/cThe surprising pairing of 2-aminoimidazo[1,2-a]- [1,3,5]triazin-4-one, a component of an expandedSynthetic biologists demonstrate their command over natural biology by reproducing the behaviors of natural living systems on synthetic biomolecular platforms. For nucleic acids, this is being done stepwise, first by adding replicable nucleotides to DNA, and then removing its standard nucleotides. This challenge has been met in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, the close contacts between particular atom types can be highlighted in so-called resolved fingerprint plots, [ 29 ] which allows the facile assignment of an intermolecular contact to a certain type of interaction and quantitatively summarize the nature and type of intermolecular contacts. The Hirshfeld surfaces are mapped with d norm , d e , and 2D fingerprint plots presented were generated using Crystal-Explorer 17.5 [ 32 , 33 , 34 , 35 , 36 ]. As can be seen from the results of the contact analysis, presented in Figure 3 and summarized in Table 1 , H-X interactions account for 84.8% of all contacts, signifying a highly compact solid-state structure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the close contacts between particular atom types can be highlighted in so-called resolved fingerprint plots, [ 29 ] which allows the facile assignment of an intermolecular contact to a certain type of interaction and quantitatively summarize the nature and type of intermolecular contacts. The Hirshfeld surfaces are mapped with d norm , d e , and 2D fingerprint plots presented were generated using Crystal-Explorer 17.5 [ 32 , 33 , 34 , 35 , 36 ]. As can be seen from the results of the contact analysis, presented in Figure 3 and summarized in Table 1 , H-X interactions account for 84.8% of all contacts, signifying a highly compact solid-state structure.…”
Section: Resultsmentioning
confidence: 99%
“…1. 22,23 In order to gain insight into the physical properties of the protonated Z nucleobase, we have investigated the relative energetics of the different protomeric forms of ZÁH + using electronic structure methods. The three lowest-energy ZÁH + protomers, optimised at the MP2/cc-pVTZ level of theory, are shown in Fig.…”
Section: Quantum Chemical Calculations Of Protomeric Forms Of Záh +mentioning
confidence: 99%
“…18,19 Indeed, studies of Z:P have shown that this UBP closely mimics G:C in terms of geometry and stability, 20,21 as well as displaying excellent replication by cellular components. 22,23 All of these features indicate that the Z:P pair has excellent potential for future biotechnology applications. Furthermore, the presence of the unique NO 2 group functionality of Z may offer selective recognition by proteins, hence facilitating novel clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Similar atomic substitution has previously been shown to dramatically influence the photochemical and photophysical properties of a DNA or RNA molecule (21,44–49). Importantly, the WC base edge is maintained and has been shown to HB with its Hachimoji conjugate base 6‐amino‐5‐nitro‐2‐pyrimidinone (Z) (18,22,43,50).…”
Section: Introductionmentioning
confidence: 99%